TWO PAULINES TO CHOOSE FROM An interview with Simon Hunt/Pauline Pantsdown. (4th October 2015) - HUNT, SIMON; STRATTON, JON
Abstract : This interview and the previous two articles constitute a mini-dossier analysing the nature and significance of the controversy over Australian academic and sound performer Simon Hunt's Pauline Pantsdown persona (as enacted on recordings, in public appearances and publicity material) and its relationship to Australian right-wing politician Pauline Hanson. Jon Stratton's extended analysis is complemented by two supporting articles, an interview with Simon Hunt conducted by Stratton and an essay by Hunt submitted to the Australian Broadcasting Corporation at their invitation. Stratton's article serves as an introduction to the interview and Hunt's essay (avoiding unnecessary duplication of content between the pieces).